Autism and trichotillomania in an adolescent boy - Masiran, Ruziana (BMJ Publishing Group, 2018)
An adolescent with autism spectrum disorder and improperly treated attention deficit hyperactivity disorder presented with recurrent hair pulling. Treatment with selective serotonin reuptake inhibitor and stimulant improved these conditions.